Modeling the epidemiology and the transmission dynamics of HIV/AIDS in a heterosexual population: basic models and analysis of local stability (2011)
Heterosexual dynamical models for HIV transmission in Nigeria are studied with the population divided into Susceptible, Infectious and AIDS compartments each for the male and female subpopulations. We assume that the AIDS compartment does not participate in sexual activities that could further cause infections among the susceptibles. The disease free and the endemic equilibria of the systems are studied analytically. The asymptotic behaviour of the endemic conditions of the systems is studied numerically. It is observed that both the disease free and the endemic equilibria for the systems are Locally Asymptotically Stable (LAS). Given uniform parameters (except for the global parameters), infections among females are observed to be relatively higher than infections among males.